2007
DOI: 10.1093/ndt/gfm309
|View full text |Cite
|
Sign up to set email alerts
|

Impact of kidney transplantation on sleep apnoea in patients with end-stage renal disease

Abstract: Background. Sleep apnoea is common in patients with end-stage renal disease. Although individual case reports have described an improvement in sleep apnoea following kidney transplantation, there have been no longitudinal studies of a case series to determine what proportion of patients with sleep apnoea improve. Methods. Dialysis-dependent patients awaiting kidney transplantation and pre-dialysis patients with an identified living donor kidney had overnight polysomnography, which was repeated several months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
3
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 30 publications
4
52
3
6
Order By: Relevance
“…Previously, we found that the prevalence of high risk for OSAS is approximately 30% in both WL and Tx patients (11). A case series indicated that AHI did not change after transplantation in 73% of the patients (12). Conversely, Mallamaci et al (13) recently reported that 22% of renal Tx recipients had a respiratory disturbance index Ͼ5, which was similar to results seen in the general population.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Previously, we found that the prevalence of high risk for OSAS is approximately 30% in both WL and Tx patients (11). A case series indicated that AHI did not change after transplantation in 73% of the patients (12). Conversely, Mallamaci et al (13) recently reported that 22% of renal Tx recipients had a respiratory disturbance index Ͼ5, which was similar to results seen in the general population.…”
supporting
confidence: 69%
“…Our previous results (11) and a case series (12), however, suggested that the risk for OSA may not improve substantially after transplantation. We hypothesized, therefore, that the prevalence of OSA would be similar in Tx versus WL patients.…”
Section: Discussionmentioning
confidence: 81%
“…Laboratory-assessed PSG studies among the kTx recipient population included much fewer patients (n 1 = 18; n 2 = 9; n 3 = 34, respectively) and mainly focused on sleep apnea and the change of the sleep structure associated with apnea treatment or transplantation. [56][57][58] Although some sleep macrostructure parameters were reported in these studies, little attention was paid to stage 2 sleep or REM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier PSG studies among kTx recipients the proportion of REM sleep was variable, from normal (21.6 ± 5.9%; 18.9 ± 8.3%) 56,58 to low (14 ± 9.2%). 57 REM latency was only reported in one study (133 ± 76 minutes).…”
mentioning
confidence: 86%
See 1 more Smart Citation